Funding Instruction for local authorities in the support of the United Kingdom’s Afghan Schemes : Locally Engaged Staff Ex Gratia (LES), Afghan Relocations and Assistance Policy (ARAP) and Afghan Citizens Resettlement Scheme (ACRS) plus eligible British Nationals : Hotel and Temporary Accommodation Wraparound Support : Financial Year 2023-2024.: Locally Engaged Staff Ex Gratia (LES), Afghan Relocations and Assistance Policy (ARAP) and Afghan Citizens Resettlement Scheme (ACRS) plus eligible British Nationals : Hotel and Temporary Accommodation Wraparound Support : Financial Year 2023-2024. (2023) - Unknown
No abstract available